UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP BILANGAN SATU SAMPAI LIMA MELALUI KEGIATAN BERMAIN PLASTISIN BAGI ANAK TUNAGRAHITA SEDANG - Yunita Mulatsih (Universitas Negeri Padang, 2015)
ABSTRACT: The background of this research is because of the problem that is found in the field where a student in a middle class of DIII/ C1 SDLBN 04 Tarantang get difficult in understand number one until five. So that trough playing plastisin students can learn how to count the number in the class and automatically it can increase the quality of the students in SDLBN 04 Tarantang Kab. Lima Puluh Kota. This research is using Single Subject Research methods with A-B-A condition. Baseline Condition (A1) is a based ability of the student in counting numbers. (B) Intervensi Condition is ATG ability after the student plays plastisin, (A2) Baseline Condition is the student ability where the play is not given. Behaviour target in this research is student can understand number one until five that can be seen the result with percentage. Data analyse in this research is using a grafic visual analyse. Kata Kunci: Anak Tunagrahita Sedang; Konsep Bilangan; Kegiatan Bermain Plastisin.